The Value And Strength Of Evidence Of The Testimonium De Auditu Witness In The Case Of Sexual Abuse Of Children - Vincentius Patria Setyawan (Gudang Jurnal Multidisiplin Ilmu, 2023)
Disclosure of a criminal case in order to find the perpetrator of a criminal act cannot be separated from witness statements as evidence. Witness testimony that is recognized as evidence is only testimony that meets subjective and objective requirements as a witness. In this regard, problems often arise in practice regarding testimonium de auditu witnesses, related to the strength of their evidence before the trial. For certain criminal acts, finding witnesses who saw, heard and experienced the crime is not easy. For example, criminal acts of sexual abuse against children, which are difficult to find because when a criminal act of sexual abuse occurs, at that time there must be only the perpetrator and the victim. The aim of this research is to determine the value and evidentiary strength of the testimony of testimonium de auditu witnesses in the process of proving criminal acts of child molestation. This problem will be answered using normative legal research methods through case studies of Decision Number: 146/Pid.Sus/2020/PN Ktg. The results of the research in writing this article are that the evidentiary value of all evidence, including witnesses, is in the hands of the judge. Judges in determining the value and proof of evidence must pay attention to its suitability with other evidence.